The Philosophical Connotations of Popular Aerobics: Illustrated by the Case of Lesmills - Yanling Wang; Maoguo Wu (European Scientific Journal, ESJ, 2016)
This paper applies the introspection method to explore the philosophical connotations of popular aerobics by analyzing the case of Lesmills. It argues that people could maintain self-integrity and experience the sense of existence during popular aerobics exercises. Popular aerobics exercises help people increase their strength and courage substantially in addition to sharpening and deepening their human sensibility. In conclusion, this paper advocates and urges the popularization of aerobics exercises for their profound philosophical values.